Liraglutide Improves Cognitive and Neuronal Function in 3-NP Rat Model of Huntington’s Disease - Shawki, Samar M.; Saad, Mohammed A.; Rahmo, Rania M.; Wadie, Walaa; El-Abhar, Hanan S. (Frontiers in Pharmacology, 2021)
Huntington disease (HD) is an autosomal dominant inherited neurodegenerative disease characterized by progressive motor, psychiatric, and cognitive abnormalities. The antidiabetic drug liraglutide possesses a neuroprotective potential against several neurodegenerative disorders; however, its role in Huntington’s disease (HD) and the possible mechanisms/trajectories remain elusive, which is the aim of this work. Liraglutide (200 μg/kg, s.c) was administered to rats intoxicated with 3-nitropropionic acid (3-NP) for 4 weeks post HD model induction. Liraglutide abated the 3-NP-induced neurobehavioral deficits (open field and elevated plus maze tests) and histopathological changes. Liraglutide downregulated the striatal mRNA expression of HSP 27, PBR and GFAP, while it upregulated that of DARPP32. On the molecular level, liraglutide enhanced striatal miR-130a gene expression and TrKB protein expression and its ligand BDNF, while reduced the striatal protein content and mRNA expression of the death receptors sortilin and p75NTR, respectively. It enhanced the neuroprotective molecules cAMP, p-PI3K, p-Akt and p-CREB, besides modulating the p-GSK-3β/p-β-catenin axis. Liraglutide enhanced the antioxidant transcription factor Nrf2, abrogated TBARS, upregulated both Bcl2 and Bcl-XL and downregulated Bax along with decreasing caspase-3 activity. Therefore, liraglutide exerts a neurotherapeutic effect on 3-NP treated rats that is, besides the upturn of behavioural and structural findings, it at least partially, increased miR-130a and modulated PI3K/Akt/CREB/BDNF/TrKB, sortilin and p75NTR, and Akt/GSK-3β/p-β-catenin trajectories besides its capacity to decrease apoptosis and oxidative stress, as well as its neurotrophic activity.